Potencial de biomassas lignocelulósicas para produção de xilose redutase - Lemos, Leanderson Túlio Marques (2022)
Lignocellulosic residues are materials with considerable possibility of reuse. The use of this material as a source of nutrients for the biotechnological production of sweeteners is a trend in studies with yeasts of the genus Candida. These yeasts can produce the enzymatic extract of xylose reductase, in addition to xylitol by the action of these enzymes responsible for metabolizing xylose. Based on this, the study aimed to evaluate the potential of these lignocellulosic residues in the production of xylose reductase. The residues were hydrolyzed according to parameters optimized by factorial design. According to the data obtained, the hydrolysis of pineapple bagasse indicated that the best hydrolysis conditions studied are: acid concentration 1.0g/L (-1); temperature 125°C (+1); time 10 min (-1). The kinetics of the specific activity of the xylose reductase enzymes allowed the perception of the peak of activity in the time of 28h of culture (0.381 U/mgproteins). The Aqueous Biphasic Systems (BAS) showed a recovery of 97.26% of the enzymes, a purification factor of 7.05 ± 0.15 of the enzymatic extract and an enzyme partition coefficient of 14.75 in the assay with the highest concentration of polymer and minor phosphate salt. In this way, it was possible to affirm that the hydrolyzed liquor from the pineapple peel has potential for fermentation and production of high added value bioproducts. The formation of low concentration of inhibitors for yeast metabolism proved to be important for the efficiency in the conversion of xylose to xylitol. In relation to the enzymatic activity of XR, this was maximum in the period of greatest conversion of substrate into product. The SABs formed by PEG 1500 and potassium phosphate showed the ability to partition and recover XR enzymes.